P744 Therapeutic gain of continued, long-term infliximab therapy in Crohn's disease patients with response but non-remission after one year of infliximab therapy. (16th January 2018) - Buhl, S; Borghede, M K; Brynskov, J; Steenholdt, C; Rasmussen, M; Ainsworth, M A
Abstract: Background: Crohn's disease patients with long-term response but non-remission to anti-tumour necrosis factor alpha treatment with infliximab have reduced disease activity, but they still have symptoms or objective signs of residual mucosal inflammation, or both, and represent a challenging population for clinicians. There is no consensus on how to handle these patients. In this study, we examined if patients with response but non-remission after one year of infliximab therapy benefit from continued infliximab therapy. Methods: Retrospective, single-centre, cohort study of Crohn's disease patients who after one year of infliximab treatment had response but non-remission to therapy. Response but non-remission was defined as clinical improvement or decrease in objective markers of disease activity; albeit, without attaining remission. Results: In total, 376 Crohn's disease patients received infliximab. Among these, 76 (20%) had response to infliximab but non-remission as evaluated after one year of scheduled infliximab maintenance therapy. The majority of these patients (64%) had non-remission due to luminal symptoms, or mucosal activity, or both; whereas 36% had either isolated or concomitant perianal fistulising activity (Figure). After another year of continued infliximab therapy, the vast majority (54/76; 71%) experienced no additional therapeutic benefit, still having response but non-remission. Only 25% (19/76) obtained remission, whereas 4% (3/76) developed secondary treatment failure (Figure). Infliximab therapy beyond two years (median follow-up 150 weeks, Interquartile range 102–237) resulted in a higher proportion of patients improving (39.5%); however, nearly half of the patients (46.1%) still failed to improve further. In a subgroup of patients ( n = 21) who discontinued infliximab while having response but non-remission, half ( n = 11) experienced disease flare after median 22 (IQR:12–31) weeks from last infliximab administration, whereas the other half had no disease change or actually improved. Conclusions: Most patients with response but non-remission after one year of infliximab therapy did not attain remission despite continued long-term infliximab therapy. Considering the growing evidence of the clinical importance of achieving remission (clinically and endoscopically), these patients have an unmet medical need.